User acceptance of technology - a case study of E-Syariah system / Rozita Mengen, Sabiroh Md.Sabri and Md Lehan Parimun - Mengen, Rozita; Md.Sabri, Sabiroh; Parimun, Md Lehan (Research Management Institute (RMI), 2010)
In IS research, the study on user's acceptance of information system has always been an interest when a new system is developed and implemented. Information system is developed to improve productivity and increase efficiency in an organization. For technologies to improve productivity, they must be accepted and used by employees in organizations. (Hu et al. 1999). In Malaysia, the Electronic Government initiative was launched to lead the country into the Information Age. It is hoped to improve how the government operates internally, as well as how it delivers services to the people of Malaysia. It seeks to improve the convenience, accessibility and quality of interactions with citizens and businesses. At the same time, it will improve information flows and processes within government to improve the speed and quality of policy development, coordination and enforcement. Under the seven pilot projects of the Electronic Government Flagship Application is the E-Syariah, which has been launched on 7th February 2003 with aims to revolutionize and bring effective changes to the operations of the Syariah Courts. E-Syariah is a system built with the objective of improving the overall efficiency and decision-making process of the Malaysian Syariah court. According to Y. Bhg. Tan Sri Samsudin Bin Osman in his keynote speech during the Government Leaders Conference 2005, the Government must determine an effective way to measure the return on public sector investment in these delivery channels in terms of the actual adoption of electronic services and how governments turn that adoption into value. This study was conducted to measure the user acceptance of E-Syariah system and to evaluate whether the acceptance of the system has lead to the usage of the system and subsequently help to improve the organization efficiency. The results of this study can be used by the organization to improve its services to the citizen as vision by the Government.